Corporate distress and turnaround: integrating the literature and directing future research - Lars Schweizer; Andreas Nienhaus (Business Research, 2017)
The topic of corporate distress and turnaround has been of interest to organizational change theory for many decades. This article considers existing reviews in discussing the current body of turnaround literature across multiple research fields and structures its work along a holistic framework. The numerous facets of corporate turnaround, resorting to general corporate restructuring research classifications, are clustered in a more detailed manner than those that merely rely on two commonly employed turnaround dimensions: 'retrenchment' and 'recovery.' The authors develop an agenda for future research based on this cross-disciplinary literature aggregation by highlighting current gaps and offering potential research questions. The review contributes to the understanding of corporate distress and turnaround by integrating different research streams. Additionally, the work emphasizes the need for further harmonization and operationalization in turnaround success metrics.
Keywords: 650; Turnaround; Corporate distress; Restructuring; Bankruptcy; Crisis; Reorganization